The efficiency of the distribution of liquid gas production plants in Sadr City - Khalifa, Sattar Jabbar (Al-Adab Journal, 2022)
The study area is one of the areas characterized by a high rate of population growth, which requires planning appropriate to this increase, especially with regard to providing the necessary services, especially energy sources, including the provision of liquid gas for use in several areas, as the population of Sadr City in 2020 reached (1276249) people, Except for the residents of the added and random areas, where this increase put a great pressure on the gas filling plants represented by the Hay Tariq gas filling plant and the granular gas filling plant, as these plants cannot cover the annual per capita quota, which is three cylinders according to the standard of the Ministry of Oil, as the share of The individual in Sadr City is only two cylinders per year.